Trip distribution in UiTM Shah Alam / Rosniza Abdul Jalil - Abdul Jalil, Rosniza (2006)
Forecasting travel demand is the “four step process” of trip generation, trip distribution, modal choice and traffic assignment. Trip generation is the process of determining the number of trips that will begin or end in each zone within a study area. Trip distribution defined as a process by which the trips generated in zone are allocated to other zone in the study area. Mode choice is the aspect of demand analysis process that determines the number (or percentage) of trips between zone that are made by automobile and by transit. Traffic assignment is to determine the actual street and highway routes that will be used and the number of automobiles and buses that can be expected on each highway segment. There are many factors influence travel demand: the location and intensity of land use, the socioeconomic characteristics of people living in the area, cost and quality of available transportation services (Garber and Hoel, 2002). The trip distribution is important in planning of future development in certain study area. There are two methods of conducting data collection: field survey and questionnaire. The trip distribution is determined from traffic volume counts. Then, the correlation between trip distribution with vehicle ownership, population of staffs and students and gross floor area is analyzed. All the factors are influenced the trip distribution in UiTM.